Observation technique and processing strategy of GPS buoy for ocean sur-face monitoring - Anuar, M.S. (2015)
This study presents a kinematic positioning approach which is use the GPS buoy for precise ocean surface monitoring. A field test was done to validate observation technique and processing strategies for this study. Observation were done at three stations with different distant to control station. Then the observation technique applied during field observation off the Senggarang coast. A GPS buoy data from field observation has been processes during a precise,medium- range differential kinematic technique' The data was collected for more than 24 hours at nearby coastal site at a high rate (1 Hz), along with measurements from neighbouring tidal stations' to verify the estimated sea surface heights' Kinematic coordinates of GPS ;;"y were estimated using the epoch-wise pre-elimination and the backward substitution algorithm. Test results show the centimeter level- accuracy in sea surface height determination can be successfully achieved using proposed technique' The centimeter level agreement between two methods also suggests it possibility of using this inexpensive and more flexible GPS buoy equiipment to enhance (or even replace) the current use of tidal gauge stations.